Technical efficiency of wrestlers in relation to some anthropometric and motor variables - Cvetkovic, C.; Maric, J.; Marelic, N. (Kinesiology, 2005)
Numerous previous studies have determined the influence of energy capacities and of motor and morphological characteristics on performance in wrestling. Research into the influence of various anthropological subspaces and motor abilities on wrestling techniques on the one hand, and the research into the interrelationship between these subspaces and abilities and wrestling techniques on the other produces valuable perceptions that can be applied in the training process both in wrestlers and in non-wrestlers (pupils, students, members of the police and army forces). The sample was comprised of 72 wrestlers (age 16-20yrs) tested at the same time at the beginning of sports preparations of young wrestlers for the European and World Championships. The measured variables encompassed two anthropometric tests (body height, body weight) and 15 motor tests. Multiple regression coefficients were used to determine the influence of those predictor variables on the following throws: take-down, arm throw, hip headlock throw, throw and arm lock and shoulder block. The significant correlation between the set of predictor variables with three wrestling techniques was established. By employing the classical regression analysis it was possible to explain 36-41% of the variance of predictor variables in the three wrestling techniques (hip headlock throw, take-down and throw). The variables that were significant in prediction were throwing the medicine ball from supine position, 20-meter run from the standing start, double hand-tapping and push-ups on the floor. It is also interesting to point out the negative influence of anthropometric measures on the execution of this throwing technique in wrestling. The obtained results allow the conclusion that technical efficiency in young top-level wrestlers depends on a large number of motor abilities as well as some morphological characteristics like body weight.